[Review] 트라이볼로지 관점에서의 그래핀 분자시뮬레이션 연구동향 - 김현준(Hyun-Joon Kim); 정구현(Koo-Hyun Chung) (Tribology and Lubricants, 2020)
Recently, graphene has attracted considerable attention owing to its unique electrical, optical, thermal, and mechanical properties. The broad spectrum of applications from optics, sensors, and electronics to biodevice have been proposed based on these properties. In particular, graphene has been proposed as a protective coating layer and solid lubricant for microdevices and nanodevices because of its high mechanical strength, chemical inertness, and low friction characteristics. During the past decade, extensive efforts have been made to explore the tribological characteristics of graphene under various conditions and to expand its applicability. In addition to the experimental approaches, the molecular simulations performed provide fundamental insights into the friction and wear characteristics of graphene resulting from molecular interactions. This work is a review of the studies conducted over the past decade on the tribological characteristics of graphene using molecular simulation. These studies demonstrate the principal mechanisms of the superlubricity of graphene and help clarify the influences of surface conditions on tribological behavior. In particular, the investigation of the effects of the number of layers, strength of adhesion to the substrate, surface roughness, and commensurability provides deeper insights into the tribological characteristics of graphene. These fundamental understandings can help elucidate the feasibility of graphene as a protective coating layer and solid lubricant for microdevices and nanodevices.